Comparisons of the anthropometric and physical characteristics of young elite Chinese male soccer players by age and playing position - Sun, Z.; Liu, X.; Fu, H.; Shen, S.; Zhou, X. (BMC Sports Science, Medicine and Rehabilitation, 2025)
This study aimed to compare the anthropometric and physical characteristics of elite 15-, 16-, and 17-year-old male soccer players by playing position. We recruited 238 players under 17 years of age from Chinese professional soccer clubs. The measurements included body height and mass, body girth and length, and body composition. The countermovement jump (CMJ), T-test, and Yo-Yo intermittent recovery test level 1 (YYIR1) were used to assess physical ability. The results revealed that the U16 and U17 players had significantly greater body mass (p < 0.05), body height (p < 0.05), muscle mass (p < 0.05), lower limb length (p < 0.05), and chest girth (p < 0.05) than did the U15 players. Significant differences in calf girth (p < 0.001), thigh girth (p < 0.05), and Achilles tendon length (p < 0.05) were observed between the U17 group and U15 group. Additionally, the U16 group and U17 group both scored significantly better than the U15 group on the 5-m sprinting test, 20-m sprinting test, 30-m sprinting test (p < 0.001), single left jump test with arm swing (p < 0.001), single right jump test with arm swing (p < 0.001), T-test (p < 0.001), CMJ test (p < 0.001), and YYIR test (p < 0.001). Furthermore, U17 players performed significantly better on the CMJ test (p < 0.001) and YYIR test (p < 0.001) than U16 players did. This study revealed significant differences in body height, body mass, muscle mass, chest girth, lower limb length, ankle circumference, calf length, Achilles tendon length, 20-m speed, 30-m speed, and YYIR test results among the six playing position groups. Goalkeepers and central defenders had significantly greater body heights than players at other playing positions. Goalkeepers scored significantly lower on the YYIR test than players in other positions did. These findings revealed the anthropometric and physical characteristics of elite 15-17-year-old male soccer players in China, helping soccer coaches better understand the anthropometric and physical characteristics across ages and playing positions when selecting youth soccer players and optimizing soccer training programs. Moreover, youth soccer players can gain insights into their own strengths and weaknesses, enabling them to develop training for personal improvement.